KAJIAN OPTIMALISASI PELAYANAN ONLINE BERITA DESO DAN ADMINISTRASI BERBASIS ELEKTRONIK GOVERNMENT DI KECAMATAN PLOSO DAN KABUPATEN JOMBANG - Girsang, Kevin Crhistoper; Fanida, Eva Hany (Publika, 2024)
SABDOPALON E-Office application is one of the innovations based on Electronic Government that was deliberately created to improve the public services of the Jombang Regency government and to realize Jombang Regency as a Smart City so as to reflect the effective and efficient services of the village government. However, in the implementation of this application there are still obstacles such as, often experiencing lagging on the server on the website, so the application of services submitted by the community has a slight delay. The purpose of this study was to describe the SABDOPALON E-Office application in Kebon Agung Village, Ploso District, Jombang Regency. The method used is a qualitative descriptive method. The focus of this study used E-Gov success factors according to (Ishengoma, Mselle, Mongi, 2019). The research method used is descriptive with a qualitative approach. The study was conducted in Kebonagung Village using observation techniques, interviews, and documentation. This study uses narrative analysis techniques including data collection, data reduction, data presentation and conclusion drawing. The results of the study showed that the implementation of SABDOPALON E-Office application can be said to be going well. However, there are still some obstacles that need to be corrected, such as lagging on the website server so that the requested services often experience delays, lack of socialization about the SABDOPALON E-Office application. Based on the results of the research, suggestions that can be given are 1) The need for efforts from the Kebonagung Village Government in providing population data in the form of data encryption so that information in the form of population data is more secure and guaranteed 2) The need to increase server capacity on the website of the E-Office application SABDOPALON 3) The need to have data backup or data backup 4) The need to add as many employees as one person